2010
DOI: 10.1248/bpb.33.1561
|View full text |Cite
|
Sign up to set email alerts
|

Oral Sustained Release Tablets of Zidovudine Using Binary Blends of Natural and Synthetic Polymers

Abstract: Oral sustained release matrix tablets of zidovudine (ZDV) were prepared using different types, proportions and blends of carbopol 71G (C71) and a plant gum obtained from Abelmoschus esculentus (AEG). The effect of various formulation factors like polymer proportion, polymer type and pH of the dissolution medium on the in vitro release of the drug was studied, using the half change technique, in 900 ml of dissolution medium, at 100 rpm. Release kinetics were analyzed using Zero-order, Higuchi's square-root and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Before drugs can be absorbed, it must first dissolve in biological fluids; therefore, dissolution test is a very critical quality parameter for solid dosage forms. The type of excipients and/or additives as well as the formulation technology have been shown to affect the dissolution, hence absorption and consequently, the expected therapeutic effect 10,11 of solid pharmaceutical forms for oral use. According to the official compendia, at least 85 % of the drug should be dissolved after 45 minutes of subjecting an uncoated tablet to dissolution test.…”
Section: Resultsmentioning
confidence: 99%
“…Before drugs can be absorbed, it must first dissolve in biological fluids; therefore, dissolution test is a very critical quality parameter for solid dosage forms. The type of excipients and/or additives as well as the formulation technology have been shown to affect the dissolution, hence absorption and consequently, the expected therapeutic effect 10,11 of solid pharmaceutical forms for oral use. According to the official compendia, at least 85 % of the drug should be dissolved after 45 minutes of subjecting an uncoated tablet to dissolution test.…”
Section: Resultsmentioning
confidence: 99%
“…Angle of repose ranged from 22.32 to 32.07°indicating that all the granules had a reasonable flow potential. According to Staniforth (13), angles close to 25°correspond to very good flow properties. Our results show that, apart from batches F2 (containing Carbopol alone), F6 (containing EC alone) and F16 (containing a blend of Carbopol and SCMC 3:1), all other batches showed very good flow.…”
Section: Micromeritic Properties Of Granulesmentioning
confidence: 99%
“…This may be attributed to the hydrophobic nature of EC which may adsorb water molecules usually associated with Carbopol formulations. Compressibility index (CI) is an indicator of changes that occur in the packing arrangement powder tapping, and is a direct measure of the propensity of a powder to consolidate while undergoing vibration, shipping and handling (13) Table II shows that the compressibility index was highest for batch F3 (containing 30 % Carbopol) which expectedly had a low flow rate. However, blending Carbopol with EC (F7-F9) or SCMC (F16-F18) significantly (p < 0.05) reduced the CI values, implying that these polymer additives improved the flowability of Carbopol polymer.…”
Section: Micromeritic Properties Of Granulesmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the several studies reported to date on AZT sustained release formulations, seeking an optimized therapy for HIV/AIDS [30][31][32][33][34][35][36][37][38][39][40][41] , no reports have been found on their prospective clinical application. However, the severity of HIV and its related disorders urges for reliable strategies on oral sustained release formulations, particularly regarding AZT.…”
Section: Research Articlementioning
confidence: 99%